Tác động của năng lực quốc gia về logistics đến xuất khẩu: Nghiên cứu thực tiễn tại Việt Nam - Pham Ho Ha , Tram; Dinh Tran Thanh , My (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study employs the gravity model and panel data of 84 countries to analyze the impact of logistics performance on Vietnam's exports during the period 2007–2018. The findings show that the logistics performance of Vietnam and the importing country has an impact on enhancing Vietnam's export value. Furthermore, the study shows that the logistics performance of Vietnam has a larger influence on Vietnam's export value than the logistics performance of the importing country. Regarding elements of logistics activities, those related to the ease of arranging competitively priced shipments, the frequency of on-time arrivals, and the competency and quality of logistics services are elements that have been proven to have the most significant influence in explaining the role of logistics in the country's exports. This study has confirmed the robustness of the model by replacing alternative measures for the country's logistics performance and dealing with endogeneity problems by applying the instrumental variable two-stage regression method.
Keywords: Gravity model; Logistics performance; Logistics Performance Index; Trade facilitation; Vietnam